China's Emerging Role in Africa : Part of the Changing Landscape of Infrastructure Finance - Foster, Vivien; Butterfield, William; Chen, Chuan; Pushak, Nataliya (World Bank, Washington, DC, 2012)
In 2006, which China named the "Year of Africa," it quadrupled its investment commitments to infrastructure in Sub-Saharan Africa, to more than $7 billion. In 2007 China committed another $4.5 billion. Such funds could make a significant contribution toward meeting Africa's infrastructure investment needs. In the power sector, where Africa faces some of its largest gaps, China is investing $5.3 billion, including $3.3 billion in projects that, if completed, will increase the region's hydro generation capacity by 30 percent. China's growing role in Africa has generated much discussion. A new study seeks to add concrete numbers and solid analysis.